(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The objective of the present study was to prepare microspheres with small size and good sphericity by spray drying technology using Isoniazid (INH) as model drug, chitosan as encapsulating polymer; lactose and L Leucine as bulking and dispersing agent respectively. Influence of formulation components on physical properties and aerosol performance were studied. The spray dried powders obtained were characterized for morphological characteristics, compatibility using scanning electron microscopy and Differential Scanning calorimetery respectively. Tapped density; bulk density and aerosol properties like Fine particle fraction, mass median aerodynamic diameter etc were also evaluated. The smooth microspheres with particle size ranging between 4 to 6 µm were obtained. The drug content of chitosan microspheres loaded with Isoniazid were in the range of 88 % to 108 %. The drug release studies showed that more than 90% of drug released from the chitosan microsphere matrix within one hour. The fine particle fraction observed between 55 to 67 % which indicate good lung deposition. Results of Fine particle fraction also revealed addition of L Leucine found to enhance powder dispersibility.